2012
DOI: 10.1159/000336746
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Cingulotomy and Anterior Capsulotomy Applied to Patients with Aggressiveness

Abstract: Objective: To perform a preliminary study on the effects and safety of bilateral cingulotomy and anterior capsulotomy in patients with aggressive behavior. Patients and Methods: Twenty-three psychiatric patients showing aggressive behavior refractory to conventional treatment were initially evaluated. The subjects were clinically selected using the Overt Aggression Scale (OAS) and the Global Assessment of Functioning Scale (GAF). Each case was carefully reviewed by the Ethics Committee of Mexico’s General Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 57 publications
1
39
0
3
Order By: Relevance
“…Secondly, there are case reports indicating the possible effects of bilateral anterior capsulotomy in schizophrenia. Jimenez et al [39] reported that combined bilateral anterior capsulotomy and cingulotomy successfully reduced aggressive behavior and improved clinical evaluations in 23 schizophrenia patients. Lastly, the anterior limb of the internal capsule (ALIC) serves as a relay route between cortical structures (such as prefrontal cortex, PFC) and the thalamus; the dorsolateral PFC region of the frontal lobe is involved in attention, affect and working memory, all of which are reported to be abnormal in schizophrenia [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there are case reports indicating the possible effects of bilateral anterior capsulotomy in schizophrenia. Jimenez et al [39] reported that combined bilateral anterior capsulotomy and cingulotomy successfully reduced aggressive behavior and improved clinical evaluations in 23 schizophrenia patients. Lastly, the anterior limb of the internal capsule (ALIC) serves as a relay route between cortical structures (such as prefrontal cortex, PFC) and the thalamus; the dorsolateral PFC region of the frontal lobe is involved in attention, affect and working memory, all of which are reported to be abnormal in schizophrenia [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate a lot the interest in our paper ‘Bilateral cingulotomy and anterior capsulotomy applied to patients with aggressiveness' published in Stereotactic and Functional Neurosurgery [1]. However, Lévêque et al wrote the title as ‘Bilateral anterior capsulotomy and cingulotomy applied to patients with aggressiveness' [2].…”
Section: Figmentioning
confidence: 99%
“…In the first series reported [3], 12 patients underwent bilateral anterior capsulotomy and cingulotomy and were evaluated by the Mayo-Portland Adaptability Inventory and Global Assessment Functioning Scale because those were the accessible instruments at that moment. A year later, a second series [1] was treated with the same surgery procedure but studied by the Overt Aggression Scale and Global Assessment of Functioning Scale. Those series have 4 cases in common (No.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be most useful (and ethically justified) to see a power calculation, based on an estimated effect size (e.g. taken from the study of Jimenez et al [2]) to determine the size of the sample needed to demonstrate safety and efficacy.…”
mentioning
confidence: 99%